Study of knowledge attitude and practice towards COVID-19 among patients attending a tertiary care hospital in Durg district of Chhattisgarh - Junaid, Mohd; Shinkar, Swapnil; Patil, Amol (International Journal Of Community Medicine And Public Health, 2021)
Background: Poor knowledge, attitude, and practice (KAP) patterns among patients might reflect the danger of possible high transmission of COVID-19 and the need for awareness campaigns. The need of the hour is to gauge the knowledge, awareness and practices of the people to help prevent the further outbreak of COVID-19. Methods: Questionnaire based cross sectional study was done for a period of 7 days to access the knowledge attitude and practice towards COVID-19 among patients attending a tertiary care hospital in Durg, Chhattisgarh. Results: A total of 288 people participated in the study, majority of respondents were males 53% mean age was 39±15.9 years. Overall, 80.4% of the participants had good knowledge, 68.6% of the participants had a positive attitude, 83.8% of the participants were following good practices. Gender and income influenced knowledge scores, being significantly higher in males and higher income individuals (p value <0.05) while attitude and practices scores had no significant association with gender and income group (p value >0.05). Conclusions: Though the population demonstrated decent knowledge, appropriate practice, and positive attitude towards COVID-19 at the time of outbreak there is still need of on-going health education and awareness campaigns and need of policies and intervention that are more person centred.